Will the Pandemic Crisis Covid-19 be a Turning Point in Changing and Bringing a New World Order? - Madouni, Ali (Technium Social Sciences Journal, 2020)
Abstract. As the new pandemic broke out in almost the globe, part of analysts, observers and politicians hurried to talk early about the major changes that may be caused by the new spreading pandemic in all domains ; specifically at the political and economic fields, locally and internationally ; in an attempt to bring to the surface a profound perspective on the new world transformations and division. The present article main aim is to approach and investigate the global situation before, during and after the pandemic crisis of 2019 ; in all world continents, from the WWI until the Post Cold War era, not only that, but also to determine the pandemic crisis’s effects and consequences in all sectors as well as on the international actors of the international relations , additionally ; to its impacts on some core concepts in Politics. Through this inductive paper we ; also present an extrapolation of the current world situation in the light of new-traditional struggle between the two great powers in the world : China and the United States ; beside the sweeping explanations of the pandemic outbreak through some theories.